Char Formation by Coal Injection and Its Behavior in the Blast Furnace. Issue 11 (23rd September 2020) - Born, Stefan; Babich, Alexander; van der Stel, Jan; Ho, Hai Thong; Sert, Dominique; Ansseau, Olivier; Plancq, Cyril; Pierret, Jean-Christophe; Geyer, Richard; Senk, Dieter; Pridhivi, Varsha
Abstract : There is a consensus that complete conversion of the injected pulverized coal (PC) within the raceway zone is hardly possible, particularly at high injection rates. Therefore, formation, transportation, and consumption of coal residues or char outside the raceway as well as its interaction with solid, liquid, and gaseous media present in the furnace are vital for an efficient blast furnace (BF) operation. Herein, done in the scope of a European Research Fund for Coal and Steel project, two injection coals are selected and used to produce char. Chemical, physical, petrographic, and microstructural properties of produced chars are characterized. Char behavior and its effect on coke and iron burden are examined using numerous analytical, laboratory, and pilot‐scale facilities. Next, industrial trials are performed to evaluate the extent of char transfer within the BF shaft at high PC injection rates. The results of gas and temperature measurements as well as sampling of dust give new insights regarding the impact of high coal injection rates on the BF inner state. Data generated from the experimental results are used for mathematical modelling. The effects of char on the cohesive zone thickness, position, and gas permeability are investigated. Abstract : The article comprises of results drawn on blast furnace coal injection. The study focuses on coal char formation, its properties, transfer to the BF shaft and interaction with coke and iron burden. Additionally, modelling and industrial trials focus on the study of impact of coal char on the blast furnace process parameters.